Given the equation:
![\cos \mleft(2x\mright)-cos\mleft(x\mright)=0](https://img.qammunity.org/2023/formulas/mathematics/college/meu02w6kac34oywluyj628hatrxnxrznqm.png)
First, we will express the cos (2x) in terms of cos (x) using the angle double rule:
![\cos (2x)=2\cos ^2(x)-1](https://img.qammunity.org/2023/formulas/mathematics/college/xmu2yn1ouclkynoaqmef9ldq2zjlkv4o2a.png)
So, the given equation will be:
![\begin{gathered} 2\cos ^2(x)-1-\cos (x)=0 \\ 2\cos ^2(x)-\cos (x)-1=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m7zbikjudcolqodjx6xxq30it13yadjzgb.png)
The last equation has the form of the quadratic equation, so we will factor the equation:
![\begin{gathered} (2\cos +1)(\cos x-1)=0 \\ 2\cos x+1=0\rightarrow\cos x=-(1)/(2)\rightarrow x=\cos ^(-1)(-(1)/(2))=120\degree \\ \cos x-1=0\rightarrow\cos x=1\rightarrow x=\cos ^(-1)(1)=0\degree \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m7fdxh5hdhnbken3j5g8xsin4wjprjodyr.png)
So, the answer will be option 3) x = 0° or 120°